Faktor Yang Berhubungan Dengan Kejadian HIV/AIDS Di Wilayah Kerja Puskesmas Bangkala (Window of Public Health Journal, 2025)
HIV/AIDS is a significant global health problem. According to WHO, there are 37.7 million people worldwide living with HIV, highlighting the critical role of knowledge in addressing this issue. In Jeneponto Regency, HIV/AIDS is a disease with a high prevalence, especially in the Bangkala Community Health Center (Puskesmas Bangkala) working area. This study aims to identify factors related to HIV/AIDS incidence, namely knowledge, attitudes, actions, and public perceptions. This study used a cross-sectional design with a stratified random sampling technique. Data were collected through a structured questionnaire that had been tested for validity and reliability. Data analysis was carried out using a bivariate statistical test (Chi-square). The variables studied included knowledge, attitudes, actions, and perceptions of HIV/AIDS incidence. The results showed that knowledge had a significant relationship with HIV/AIDS incidence (p-value 0.001). Respondents with low levels of knowledge were at higher risk of experiencing HIV/AIDS. Attitudes did not show a significant relationship with HIV/AIDS incidence (p-value 1.000). Preventive measures, such as condom use and HIV testing, also did not have a significant relationship with the incidence of HIV/AIDS (p-value 0.566). Risk perception also did not show a significant relationship with the incidence of HIV/AIDS (p-value 1.000). This study concluded that only knowledge had a significant relationship with the incidence of HIV/AIDS, underscoring the importance of targeted educational interventions. Further research is recommended to explore the social and economic factors that influence the incidence of HIV/AIDS, as well as consider qualitative research methods to gain a more comprehensive understanding.